Televiewing Behaviour of Rural Women towards Agricultural Programme: A Case Study in Latur, Maharashtra, India - Waghmare, P. G.; Suradkar, D. D.; Venkatesha, K. (International Journal of Economic Plants, 2015)
The aim of the study is to find out the extent of usage of agricultural programme on television by rural women, study the viewing behaviour and time spent for agricultural programme and identify the preferences of rural women with reference to agricultural programmes on television. The findings of the study is majority 60.94 of the respondents belonged to middle age group, 32.03% educated up to secondary school level, 81.26% rural women had medium family size, 81.25% of rural women had medium annual income, higher percentage 64.84% of respondents were found in medium land holding category, (82.03%) of the rural women had medium social participation, 70.31% of the respondents had medium level of mass media use, 64.84% of rural women had medium level of extension contact, 77.34% had medium level of socio-economics status, majority of the respondents (65.62%) had purchased television sets in between 3 to 4 years, (92.18%) viewed channel star plus, the credibility index was 81.80%, 92.96% of the rural women preferred entertainment programmes. As concerned to the media credibility, extent of usefulness and discuss of programmes only age was positively and significantly related. At the same time there was no other independent variable like education, family size, annual income, land holding, social participation, mass media use, extension contact and socio economic status had non-significant relationship. It was revealed that, 100% of the respondents expressed the problem was electricity problem and 88.28% respondent expressed more commercial breaks. Majority of the respondents said that lack of time (60.15%), information is not timely (59.37%), use of difficult terms (44.53%), inconvenient time (28.90%), too much information in less time (27.34%).